Tide of the Time: Global tidal characteristics observed from in-situ measurements - Michael G. Hart-Davis; Roman Sulzbach; Stefan A. Talke; Ivan D. Haigh; Marta Marcos; Philip Woodworth; Richard Ray; Ole B. Andersen; Florent Lyard; Ergane Fouchet; Denise Dettmering; Maik Thomas; et al. (Ocean Science, 2026)
Tide gauges have been critical sources for sea level research, enabling the development of tidal theory and an understanding of local variations that occur across the global oceans. Tides play important roles in a variety of oceanographic and geodetic applications, and characterizing their spatial variability is valuable for applications ranging from fishing to flood risk management. This manuscript presents the coastal characteristics of ocean tides based on 3591 high-frequency tide gauge observations from the recently updated Global Extreme Sea Level Analysis (GESLA) database. These characteristics range from tidal datums such as Mean High Water (MHW) and the Great Diurnal Range to metrics like the Age of the Tide, Form Factors, updated amplitude trend estimates, and new insights into the regional duration of high tides. Our analysis finds that 125 out of 237 long-time series show statistically significant trends in one or more constituents, from −1.47 to +1.80 mm yr−1, while the duration of the high-water stand during spring tides is shown to vary from 1 to 14 h, for an inundation depth of 20 cm. It is anticipated that the results presented will be useful not only to tidal experts but also to a wide range of cross-disciplinary researchers and local communities, aiding their understanding of a vital component of the global Earth system.

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Tuning the morphology of aerosolised cellulose nanocrystal particulates via controlled aggregation - Daniel Warnes; Wenyang Xu; Jia Hui Lim; Richard M. Parker; Bruno Frka-Petesic; Ray Freshwater; Camila Honorato-Rios; Yu Ogawa; Chiara Giorio; Silvia Vignolini (Carbohydrate Polymers, 2026)

Letter to the Editor: Misclassification of fibres in Ramage et al. (2025) and implications for microplastics research - Kelly J. Sheridan; Richard S. Blackburn; Miranda T. Prendergast-Miller; Josephine Jones; Ray Palmer; Thomas Stanton (Chemosphere, 2025)

Enhancing plant and soil health through organic amendments in a humid environment - Ram L. Ray; Kusalika M. Kularathna; Richard W. Griffin; Nimal Abeysingha; Selamawit Woldesenbet; Almoutaz Elhassan; Ripendra Awal; Ali Fares (Rhizosphere, 2025)

Impacts of N-(n-Butyl)thiophosphoric triamide (NBPT) on the physicochemical properties of milk protein isolate (MPI) dispersions: A study on micelle integrity - Maria P. Byrne; Patrick J. Forrestal; Tom F. O’ Callaghan; Niharika Rahman; Aishwarya Ray; Martin Danaher; Bernard M. Corrigan; Noel A. McCarthy; Chikere G. Nkwonta; Karl Richards; Farhad Garavand; Enda Cummins; et al. (Food Structure, 2025)

Comparing voluntary and government-mandated management measures for meeting sustainable fishing targets - Michael C. Melnychuk; Samantha Lees; Pedro Veiga; Jennifer Rasal; Nicole Baker; Lauren Koerner; Daniel Hively; Hiroyuki Kurota; Carryn L. de Moor; Maite Pons; Pamela M. Mace; Ana M. Parma; et al. (Journal of Environmental Management, 2025)

Trends in the M$$_2$$ ocean tide observed by satellite altimetry in the presence of systematic errors - Richard D. Ray; Michael Schindelegger (Journal of Geodesy, 2025)
Trends in the deep-ocean M $$_2$$ 2 barotropic tide, deduced from nearly three decades of satellite altimetry and recently presented by Opel et al. (Commun Earth Environ 5:261, https://doi.org/10.1038/s43247-024-01432-5 , 2024), are here updated with a slightly longer time series and with a focus on potential systematic errors. Tidal changes are very small, of order 0.2 mm/year or less, with a tendency for decreasing amplitudes, which is evidently a response to the ocean’s increasing stratification and an increasing energy loss to baroclinic motion. A variety of systematic errors in the satellite altimeter system potentially corrupt these small trend estimates. The Dynamic Atmosphere Correction (DAC), derived from an ocean model and used for de-aliasing, introduces a spurious trend (exceeding 0.1 mm/year in places) caused by changes in ECMWF atmospheric tides. Both operational and reanalysis atmospheric tides have spurious trends over the altimeter era. Tidally coherent errors in satellite orbits, including from use of inconsistent tidal geocenter models, are more difficult to bound, although differences between two sets of satellite ephemerides are found to reach 0.1 mm/year for M $$_2$$ 2 . Orbit errors are more deleterious for some other constituents, including the annual cycle. Tidal leakage in the “mesoscale correction,” needed here to suppress non-tidal ocean variability, is a known potential problem, and if the leakage changes over time, it impacts ocean-tide trend estimation. Tests show the error is likely small in the open ocean ( $$<0.04$$ < 0.04 mm/year) but large in some marginal seas ( $$>0.2$$ > 0.2 mm/year). Potential contamination from other altimeter corrections (e.g., ionospheric path delay) is likely negligible for M $$_2$$ 2 but can be difficult to bound.

Comparative Analysis of Foundation Systems in Expansive Soil: A Three-Dimensional Model Approach to Moisture Diffusion and Volume Changes - Ammar Alnmr; Richard Ray; Mounzer Omran Alzawi (Geotechnical and Geological Engineering, 2024)
This study compares the performance of various foundation systems in expansive soils, such as mats, granular anchor piles, and concrete piles. Expansive soils experience volumetric changes due to moisture fluctuations, which can lead to structural damage. Abaqus software, in conjunction with the SCV approach, is used to analyze soil-foundation interactions. A custom subroutine enhances simulation accuracy by incorporating empirical data on unsaturated clay behavior, matric suction, and variations in effective stress. The method’s accuracy is validated by comparing simulation results to field and laboratory experiments. The findings indicate that increasing the applied load on mats decreases overall heave but increases the differential heave. Additionally, higher soil permeability dereases the differential heave of mats. Granular anchor piles outperform concrete piles by more than 50% in highly expansive soils, suggesting a preference for these foundations. This study provides insights into the behavior of expansive soils, which will assist engineers in designing resilient foundation systems for structures.

Advanced Numerical Simulation of Scour around Bridge Piers: Effects of Pier Geometry and Debris on Scour Depth - Muhanad Al-Jubouri; Richard P. Ray; Ethar H. Abbas (Journal of Marine Science and Engineering, 2024)
Investigating different pier shapes and debris Finteractions in scour patterns is vital for understanding the risks to bridge stability. This study investigates the impact of different shapes of pier and debris interactions on scour patterns using numerical simulations with flow-3D and controlled laboratory experiments. The model setup is rigorously calibrated against a physical flume experiment, incorporating a steady-state flow as the initial condition for sediment transport simulations. The Fractional Area/Volume Obstacle Representation (FAVOR) technique and the renormalized group (RNG) turbulence model enhance the simulation’s precision. The numerical results indicate that pier geometry is a critical factor influencing the scour depth. Among the tested shapes, square piers exhibit the most severe scour, with depths reaching 5.8 cm, while lenticular piers show the least scour, with a maximum depth of 2.5 cm. The study also highlights the role of horseshoe, wake, and shear layer vortices in determining scour locations, with varying impacts across different pier shapes. The Q-criterion study identified debris-induced vortex generation and intensification. The debris amount, thickness, and pier diameter (T/Y) significantly affect the scouring patterns. When dealing with high wedge (HW) debris, square piers have the largest scour depth at T/Y = 0.25, while lenticular piers exhibit a lower scour. When debris is present, the scour depth rises at T/Y = 0.5. Depending on the form of the debris, a significant fluctuation of up to 5 cm was reported. There are difficulties in precisely estimating the scour depth under complicated circumstances because of the disparity between numerical simulations and actual data, which varies from 6% for square piers with a debris relative thickness T/Y = 0.25 to 32% for cylindrical piers with T/Y = 0.5. The study demonstrates that while flow-3D simulations align reasonably well with the experimental data under a low debris impact, discrepancies increase with more complex debris interactions and higher submersion depths, particularly for cylindrical piers. The novelty of this work lies in its comprehensive approach to evaluating the effects of different pier shapes and debris interactions on scour patterns, offering new insights into the effectiveness of flow-3D simulations in predicting the scour patterns under varying conditions.

Investigating the Impact of Varying Sand Content on the Physical Characteristics of Expansive Clay Soils from Syria - Ammar Alnmr; Richard Ray (Geotechnical and Geological Engineering, 2024)
Expansive clayey soils often pose challenges for construction projects due to their low bearing capacity, swelling, and shrinkage properties. While previous research has explored additives to enhance these soils’ properties, the potential of sand remains underexplored. This study investigates the impact of varying sand percentages on expansive clayey soils’ consistency, compaction, and permeability. This study examines how adding different percentages of sand influences the physical properties of expansive clayey soils. Laboratory tests involved systematic testing of texture, compaction, and permeability. Findings reveal a notable improvement in the physical properties of the soil with the addition of sand. Results from the laboratory tests provided data for empirical equations that facilitate the prediction of soil properties based on the sand content. The enhancement in soil properties underscores the potential of sand as an additive for expansive clayey soils. The empirical equations presented here provide practical benefits to geotechnical engineers and practitioners engaged in construction projects involving these soils, offering them valuable insights into the benefits of sand additives to improve physical characteristics. The insights gained from this research hold promising prospects for improving construction practices and addressing the challenges associated with these soils.

Quota use in mixed‐stock fisheries - William A. Karp; Michael C. Melnychuk; Robyn E. Forrest; Lorne Richard Little; Kristin McQuaw; Chad Demarest; Ray Hilborn; Nicole Baker; Brian Mose; Bruce Turris; Ernesto Penas Lado (Fish and Fisheries, 2024)
Although most fisheries assessment and management focuses on the status of individual stocks, and regulations are commonly established as single‐species total allowable catch limits (TACs), much of the catch from global fisheries comes from mixed‐stock fisheries where species cannot be harvested separately. We show that in some fisheries where TAC and catch of demersal fish stocks are tracked, the average fraction of TAC harvested ranges from 21% to 68% overall and is declining. This is, in part, related to efforts to protect all species from overfishing, leading to ‘choke species’, which limit fishing pressure on other target species. While some choke species arise from a mix of low and high‐productivity species, others result from allocation processes, which can be aggravated by shifting distributions due to climate change. Underutilization of TACs can also result from market limitations, low value of individual species, undercapacity or management measures. Proposed methods for increasing long‐term yield require species to be managed in stock groups, or allowing the abundance of some stocks to fall below target reference points. We suggest that the observed low and declining aggregate harvests are due, primarily, to the focus on single‐stock sustainability measures, rather than performance of the fisheries in relation to potential overall yield. While there is a growing consensus that single‐species management should be replaced by an ecosystem‐based approach, this will require clear legislative directives regarding management of the trade‐offs involved. Time series considered in this analysis do not extend beyond 2019.

HydroShare retrospective: Science and technology advances of a comprehensive data and model publication environment for the water science domain - David G. Tarboton; Daniel P. Ames; Jeffery S. Horsburgh; Jonathan L. Goodall; Alva Couch; Richard Hooper; Jerad Bales; Shaowen Wang; Anthony Castronova; Martin Seul; Ray Idaszak; Zhiyu Li; et al. (Environmental Modelling & Software, 2024)

Ocean Circulation from Space - Rosemary Morrow; Lee-Lueng Fu; Marie-Héléne Rio; Richard Ray; Pierre Prandi; Pierre-Yves Le Traon; Jérôme Benveniste (Surveys in Geophysics, 2023)
This paper reviews the recent progress in our estimation of ocean dynamic topography and the derived surface geostrophic currents, mainly based on multiple nadir radar altimeter missions. These altimetric observations provide the cornerstone of our ocean circulation observing system from space. The largest signal in sea surface topography is from the mean surface dominated by the marine geoid, and we will discuss recent progress in observing the mean ocean circulation from altimetry, once the geoid and other corrections have been estimated and removed. We then address the recent advances in our observations of the large-scale and mesoscale ocean circulation from space, and the particular challenges and opportunities for new observations in the polar regions. The active research in the ocean barotropic tides and internal tidal circulation is also presented. The paper also addresses how our networks of global multi-satellite and in situ observations are being combined and assimilated to characterize the four-dimensional ocean circulation, for climate research and ocean forecasting systems. For the future of ocean circulation from space, the need for continuity of our current observing system is crucial, and we discuss the exciting enhancement to come with global wide-swath altimetry, the extension into the coastal and high-latitude regions, and proposals for direct total surface current satellites in the 2030 period.

Characterizing state‐managed and unmanaged fisheries in coastal marine states and territories of the United States - Michael C. Melnychuk; Charmane E. Ashbrook; Richard J. Bell; Lyall Bellquist; Kate Kauer; Jono R. Wilson; Ray Hilborn; Jay Odell (Fish and Fisheries, 2023)
The status of federally managed fisheries in the United States is well monitored, but the condition of other marine fisheries, whether state‐managed, territory‐managed or unmanaged, is less understood and often unknown. We used expert surveys to characterize the management systems of non‐federally managed fisheries in US coastal marine states and overseas territories. For 311 fisheries, we estimated an overall Fisheries Management Index (FMI) and a qualitative stock status score. These measures were positively correlated, and while a wide range of research, management, enforcement and socioeconomic criteria were partially met (FMI ≥ 0.5) for 66% of fisheries, stock status was considered as partially acceptable (score ≥ 0.5) for only 45% of fisheries and acceptable (score = 1) for only 16% of fisheries. Higher FMI was typically observed in fisheries with greater commercial landed weight, value, or greater recreational catches. Fisheries from continental states had higher FMI than those from overseas territories. Invertebrates and diadromous fish species had higher FMI on average compared to those of marine fishes. Extrapolating results for surveyed fisheries to nearly 2000 non‐federally managed US fisheries while stratifying by state and importance designation (based on commercial, recreational, cultural or ecological importance), we estimate a mean overall FMI of 0.48, and estimate that only 19% of fisheries have a reliable estimate of stock status available; both measures are lower than similar estimates for federally managed fisheries. Funding or capacity constraints and information or data limitations were identified as common challenges faced by state agencies in managing fisheries under their jurisdiction.

Modelling potential human exposure to the nitrification inhibitor dicyandiamide through the environment-food pathway - Aishwarya Ray; Patrick Forrestal; Chikere Nkwonta; Niharika Rahman; Pilar Byrne; Martin Danaher; Karl Richards; Sean Hogan; Enda Cummins (Environmental Impact Assessment Review, 2023)

Measurement of grass uptake of the urease inhibitor NBPT and of the nitrification inhibitor dicyandiamide co-applied with granular urea - Niharika Rahman; Chikere G Nkwonta; Martin Danaher; Karl G. Richards; Sean A Hogan; Enda Cummins; Macdara O’ Neill; Aishwarya Ray; Maria P. Byrne; Patrick J. Forrestal (Environmental Science and Pollution Research, 2023)

Rise and fall of SARS-CoV-2 variants in Rotterdam: Comparison of wastewater and clinical surveillance - Ray W. Izquierdo-Lara; Leo Heijnen; Bas B. Oude Munnink; Claudia M.E. Schapendonk; Goffe Elsinga; Jeroen Langeveld; Johan Post; Divyae K. Prasad; Christian Carrizosa; Frederic Been; Janko van Beek; Remy Schilperoort; et al. (Science of The Total Environment, 2023)

Modelling of the Torsional Simple Shear Test with Randomized Tresca Model Properties in Midas GTS NX - Majd Ahmad; Richard Ray (Geotechnical and Geological Engineering, 2023)
The dynamic properties of soil obtained from the torsional simple shear test (TOSS) are assumed to be uniform throughout the specimen. For some exceptional soils, this may hold true, but for the most majority of soils that we examine, it is obviously not the case, and this level of non-uniformity depends on the conditions in which the soil was formed. In this paper, we discuss a method of modelling inherently non-uniform soil specimens by representing them with elements that have an elasto-plastic simple Tresca material model with different properties (Elastic young modulus and yield stresses). The combination of properties that can simulate the nonlinear behaviour of the soil is found and calibrated using a model of the TOSS test built in the finite element software Midas GTS NX. Furthermore, the influence of rigid inclusions in the soil is studied and the results show an increase in stiffness with the increasing percentage of inclusion in the soil.

Impact of anoxia and oyster mortality on nutrient and microbial planktonic components: A mesocosm study - Julie Le Ray; Béatrice Bec; Annie Fiandrino; Franck Lagarde; Nicolas Cimiterra; Patrick Raimbault; Cécile Roques; Sylvain Rigaud; Julie Régis; Behzad Mostajir; Sébastien Mas; Marion Richard (Aquaculture, 2023)

Seasonal differences in day-roost selection by Northern long-eared bats (Myotis septentrionalis) in Louisiana and a meta-analytical comparison across North America - Carlos J. Garcia; David A. Ray; Roger W. Perry; Richard D. Stevens (Forest Ecology and Management, 2023)

Wave setup at the Minamitorishima tide gauge - Richard D. Ray; Mark A. Merrifield; Philip L. Woodworth (Journal of Oceanography, 2023)

Technical note: On seasonal variability of the M 2 tide - Richard D. Ray (Ocean Science, 2022)
Seasonal variability of the M2 ocean tide can be detected at many ports, perhaps most. Examination of the cluster of tidal constituents residing within the M2 tidal group can shed light on the physical mechanisms underlying seasonality. In the broadest terms these are astronomical, frictional–advective interactions, and climate processes; some induce annual modulations and some semiannual, in amplitude, phase, or both. This note reviews how this occurs and gives an example from each broad category. Phase conventions and their relationship with causal mechanisms, as well as nomenclature, are also addressed.

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The mean seasonal cycle in relative sea level from satellite altimetry and gravimetry - Richard D. Ray; Bryant D. Loomis; Victor Zlotnicki (Journal of Geodesy, 2021)
Satellite altimetry and gravimetry are used to determine the mean seasonal cycle in relative sea level, a quantity relevant to coastal flooding and related applications. The main harmonics (annual, semiannual, terannual) are estimated from 25 years of gridded altimetry, while several conventional altimeter “corrections” (gravitational tide, pole tide, and inverted barometer) are restored. To transform from absolute to relative sea levels, a model of vertical land motion is developed from a high-resolution seasonal mass inversion estimated from satellite gravimetry. An adjustment for annual geocenter motion accounts for use of a center-of-mass reference frame in satellite orbit determination. A set of 544 test tide gauges, from which seasonal harmonics have been estimated from hourly measurements, is used to assess how accurately each adjustment to the altimeter data helps converge the results to true relative sea levels. At these gauges, the median annual and semiannual amplitudes are 7.1 cm and 2.2 cm, respectively. The root-mean-square differences with altimetry are 3.24 and 1.17 cm, respectively, which are reduced to 1.93 and 0.86 cm after restoration of corrections and adjustment for land motion. Example outliers highlight some limitations of present-day coastal altimetry owing to inadequate spatial resolution: upwelling and currents off Oregon and wave setup at Minamitori Island.

Preface: Developments in the science and history of tides - Philip L. Woodworth; J. A. Mattias Green; Richard D. Ray; John M. Huthnance (Ocean Science, 2021)
This special issue marks the 100th anniversary of the founding of the Liverpool Tidal Institute (LTI), one of a number of important scientific developments in 1919. The preface gives a brief history of how the LTI came about and the roles of its first two directors, Joseph Proudman and Arthur Doodson. It also gives a short overview of the research on tides at the LTI through the years. Summaries are given of the 26 papers in the special issue. It will be seen that the topics of many of them could be thought of as providing a continuation of the research first undertaken at the LTI. Altogether, they provide an interesting snapshot of work on tides now being made by groups around the world.

Accuracy assessment of global internal-tide models using satellite altimetry - Loren Carrere; Brian K. Arbic; Brian Dushaw; Gary Egbert; Svetlana Erofeeva; Florent Lyard; Richard D. Ray; Clément Ubelmann; Edward Zaron; Zhongxiang Zhao; Jay F. Shriver; Maarten Cornelis Buijsman; et al. (Ocean Science, 2021)
Altimeter measurements are corrected for several geophysical parameters in order to access ocean signals of interest, like mesoscale or sub-mesoscale variability. The ocean tide is one of the most critical corrections due to the amplitude of the tidal elevations and to the aliasing phenomena of high-frequency signals into the lower-frequency band, but the internal-tide signatures at the ocean surface are not yet corrected globally. Internal tides can have a signature of several centimeters at the surface with wavelengths of about 50–250 km for the first mode and even smaller scales for higher-order modes. The goals of the upcoming Surface Water Ocean Topography (SWOT) mission and other high-resolution ocean measurements make the correction of these small-scale signals a challenge, as the correction of all tidal variability becomes mandatory to access accurate measurements of other oceanic signals. In this context, several scientific teams are working on the development of new internal-tide models, taking advantage of the very long altimeter time series now available, which represent an unprecedented and valuable global ocean database. The internal-tide models presented here focus on the coherent internal-tide signal and they are of three types: empirical models based upon analysis of existing altimeter missions, an assimilative model and a three-dimensional hydrodynamic model. A detailed comparison and validation of these internal-tide models is proposed using existing satellite altimeter databases. The analysis focuses on the four main tidal constituents: M2, K1, O1 and S2. The validation process is based on a statistical analysis of multi-mission altimetry including Jason-2 and Cryosphere Satellite-2 data. The results show a significant altimeter variance reduction when using internal-tide corrections in all ocean regions where internal tides are generating or propagating. A complementary spectral analysis also gives some estimation of the performance of each model as a function of wavelength and some insight into the residual non-stationary part of internal tides in the different regions of interest. This work led to the implementation of a new internal-tide correction (ZARON'one) in the next geophysical data records version-F (GDR-F) standards.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Cancer mortality risk, fine particulate air pollution, and smoking in a large, representative cohort of US adults - Nathan C. Coleman; Richard T. Burnett; Joshua D. Higbee; Jacob S. Lefler; Ray M. Merrill; Majid Ezzati; Julian D. Marshall; Sun-Young Kim; Matthew Bechle; Allen L. Robinson; C. Arden Pope (Cancer Causes & Control, 2020)

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Forcing Factors Affecting Sea Level Changes at the Coast - Philip L. Woodworth; Angélique Melet; Marta Marcos; Richard D. Ray; Guy Wöppelmann; Yoshi N. Sasaki; Mauro Cirano; Angela Hibbert; John M. Huthnance; Sebastià Monserrat; Mark A. Merrifield (Surveys in Geophysics, 2019)

The Development of a Canadian Integrated Ocean Observing System (CIOOS) - Andrew Stewart; Brad deYoung; Mike Smit; Karen Donaldson; Alexa Reedman; Andréane Bastien; Ray Brunsting; Bill Carter; Brad Covey; Richard Kelly; Eric Peterson; Benoît Pirenne; et al. (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

A review of regulations and guidelines related to winter manure application - Jian Liu; Peter J. A. Kleinman; Helena Aronsson; Don Flaten; Richard W. McDowell; Marianne Bechmann; Douglas B. Beegle; Timothy P. Robinson; Ray B. Bryant; Hongbin Liu; Andrew N. Sharpley; Tamie L. Veith (Ambio, 2018)

Human activity was a major driver of the mid‐Holocene vegetation change in southern Cumbria: implications for the elm decline in the British Isles - Mark J. Grosvenor; Richard T. Jones; Chris S. M. Turney; Dan J. Charman; Alan Hogg; Dave Coward; Ray Wilson (Journal of Quaternary Science, 2017)
The dramatic decline in elm ( Ulmus ) across a large swathe of north‐west Europe in the mid‐Holocene has been ascribed to a number of possible factors, including climate change, human activity and/or pathogens. A major limitation for identifying the underlying cause(s) has been the limited number of high‐resolution records with robust geochronological frameworks. Here, we report a multiproxy study of an upland (Blea Tarn) and lowland (Urswick Tarn) landscape in southern Cumbria (British Isles) to reconstruct vegetation change across the elm decline in an area with a rich and well‐dated archaeological record to disentangle different possible controls. Here we find a two‐stage decline in Ulmus taking place between 6350–6150 and 6050–5850 cal a BP, with the second phase coinciding with an intensification of human activity. The scale of the decline and associated human impact is more abrupt in the upland landscape. We consider it likely that a combination of human impact and disease drove the Ulmus decline within southern Cumbria.

Children’s head movements and postural stability as a function of task - Ian Flatters; Faisal Mushtaq; Liam J. B. Hill; Anna Rossiter; Kate Jarrett-Peet; Pete Culmer; Ray Holt; Richard M. Wilkie; Mark Mon-Williams (Experimental Brain Research, 2014)

The exo-proteome and exo-metabolome of Nostoc punctiforme (Cyanobacteria) in the presence and absence of nitrate - Laura Vilhauer; Judith Jervis; W. Keith Ray; Richard F. Helm (Archives of Microbiology, 2014)

Iron cycling at corroding carbon steel surfaces - Jason S. Lee; Joyce M. McBeth; Richard I. Ray; Brenda J. Little; David Emerson (Biofouling, 2013)

Variation in Cell Wall Composition and Accessibility in Relation to Biofuel Potential of Short Rotation Coppice Willows - Michael J. Ray; Nicholas J. B. Brereton; Ian Shield; Angela Karp; Richard J. Murphy (BioEnergy Research, 2012)

Sulphide production and corrosion in seawaters during exposure to FAME diesel - Jason S. Lee; Richard I. Ray; Brenda J. Little; Kathleen E. Duncan; Athenia L. Oldham; Irene A. Davidova; Joseph M. Suflita (Biofouling, 2012)

The sex-specific region of sex chromosomes in animals and plants - Andrea R. Gschwend; Laura A. Weingartner; Richard C. Moore; Ray Ming (Chromosome Research, 2012)

Lifelong stable human insulin expression in transgenic tilapia expressing a humanized tilapia insulin gene - Olga Hrytsenko; Gina R. Rayat; Bao-You Xu; Richard Krause; Bill Pohajdak; Ray V. Rajotte; James R. Wright (Transgenic Research, 2011)

Benthic macrofaunal compositional variations in the northern Bering Sea - Jerry McCormick-Ray; Richard M. Warwick; G. Carleton Ray (Marine Biology, 2011)

One centimeter-level observations of diurnal ocean tides from global monthly mean time-variable gravity fields - Shin-Chan Han; Richard D. Ray; Scott B. Luthcke (Journal of Geodesy, 2010)

Bottom pressure tides along a line in the southeast Atlantic Ocean and comparisons with satellite altimetry - Richard D. Ray; Deirdre A. Byrne (Ocean Dynamics, 2010)

QTL Mapping of Enzymatic Saccharification in Short Rotation Coppice Willow and Its Independence from Biomass Yield - Nicholas J. B. Brereton; Frederic E. Pitre; Steven J. Hanley; Michael J. Ray; Angela Karp; Richard J. Murphy (BioEnergy Research, 2010)

An assessment of alternative diesel fuels: microbiological contamination and corrosion under storage conditions - Jason S. Lee; Richard I. Ray; Brenda J. Little (Biofouling, 2010)

Long‐term patterns of dissolved organic carbon in lakes across eastern Canada: Evidence of a pronounced climate effect - Jan Zhang; Jeff Hudson; Richard Neal; Jeff Sereda; Thomas Clair; Michael Turner; Dean Jeffries; Peter Dillon; Lewis Molot; Keith Somers; Ray Hesslein (Limnology and Oceanography, 2010)
We analyzed the 21‐yr dynamics of dissolved organic carbon (DOC) in 55 lakes during ice‐free periods in five regions across eastern Canada in relation to total solar radiation (TSR), precipitation, air temperature, sulfate deposition (SO4), Southern Oscillation Index (SOI), North Atlantic Oscillation, and Pacific Decadal Oscillation (PDO). A synchronous pattern in DOC was found among lakes within each region; however, a synchronous pattern in DOC was not found among regions, except for Kejimkujik and Yarmouth. Long‐term trends of increasing or decreasing DOC concentration were not evident except at the Experimental Lakes Area (ELA), where an increase in DOC correlated with a decrease in summer TSR and an increase in summer precipitation. Annual mean temperature increased at the Nova Scotia and Turkey Lakes Watershed regions (TLW) over the study period, but there was no corresponding change in DOC. TSR and precipitation were important explanatory variables across all regions, except for the TLW. Summer TSR, or annual TSR, had a negative relationship, while summer precipitation had a positive relationship with the temporal DOC pattern in all regions except TLW. TSR and precipitation explained 78%, 49%, and 84% of the variation in the long‐term DOC patterns at Dorset, ELA, and Nova Scotia (NS) regions, respectively. In contrast, the long‐term pattern in DOC at TLW was only weakly related to SOI and PDO.

Cannabis and benzodiazepines as determinants of methadone trough plasma concentration variability in maintenance treatment: a transnational study - Richard Hallinan; Séverine Crettol; Kingsley Agho; John Attia; Jacques Besson; Marina Croquette-Krokar; Robert Hämmig; Jean-Jacques Déglon; Andrew Byrne; John Ray; Andrew A. Somogyi; Chin B. Eap (European Journal of Clinical Pharmacology, 2009)

Prevalence and type distribution of human papillomavirus in 5,000 British Columbia women—implications for vaccination - Richard A. Moore; Gina Ogilvie; Daniel Fornika; Veronika Moravan; Marc Brisson; Mahsa Amirabbasi-Beik; Anita Kollar; Thomas Burgess; Ray Hsu; Laura Towers; Jane Lo; Jasenka Matisic; et al. (Cancer Causes & Control, 2009)

Elevated air temperature alters an old‐field insect community in a multifactor climate change experiment - SHAWN N. VILLALPANDO; RAY S. WILLIAMS; RICHARD J. NORBY (Global Change Biology, 2009)
To address how multiple, interacting climate drivers may affect plant–insect community associations, we sampled insects that naturally colonized a constructed old‐field plant community grown for over 2 years under simultaneous CO 2 , temperature, and water manipulation. Insects were sampled using a combination of sticky traps and vacuum sampling, identified to morphospecies and the insect community with respect to abundance, richness, and evenness quantified. Individuals were assigned to four broad feeding guilds in order to examine potential trophic level effects. Although there were occasional effects of CO 2 and water treatment, the effects of warming on the insect community were large and consistent. Warming significantly increased Order Thysanoptera abundance and reduced overall morphospecies richness and evenness. Nonmetric multidimensional scaling found that only temperature affected insect community composition, while a Sørensen similarity index showed less correspondence in the insect community between temperature treatments compared with CO 2 or soil water treatments. Within the herbivore guild, elevated temperature significantly reduced richness and evenness. Corresponding reductions of diversity measures at higher trophic levels (i.e. parasitoids), along with the finding that herbivore richness was a significant predictor of parasitoid richness, suggest trophic‐level effects within the insect community. When the most abundant species were considered in temperature treatments, a small number of species increased in abundance at elevated temperature, while others declined compared with ambient temperature. Effects of temperature in the dominant insects demonstrated that treatment effects were limited to a relatively small number of morphospecies. Observed effects of elevated CO 2 concentration on whole‐community foliar N concentration did not result in any effect on herbivores, which are probably the most susceptible guild to changes in plant nutritional quality. These results demonstrate that climatic warming may alter certain insect communities via effects on insect species most responsive to a higher temperature, contributing to a change in community structure.

Characterization of Insertion Sites in Rainbow Papaya, the First Commercialized Transgenic Fruit Crop - Jon Y. Suzuki; Savarni Tripathi; Gustavo A. Fermín; Fuh-Jyh Jan; Shaobin Hou; Jimmy H. Saw; Christine M. Ackerman; Qingyi Yu; Michael C. Schatz; Karen Y. Pitz; Marcela Yépes; Maureen M. M. Fitch; et al. (Tropical Plant Biology, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Mapping nonlinear shallow-water tides: a look at the past and future - Ole B. Andersen; Gary D. Egbert; Svetlana Y. Erofeeva; Richard D. Ray (Ocean Dynamics, 2006)

Light-regulated overexpression of an Arabidopsis phytochrome A gene in rice alters plant architecture and increases grain yield - Ajay K. Garg; Ruairidh J. H. Sawers; Haiyang Wang; Ju-Kon Kim; Joseph M. Walker; Thomas P. Brutnell; Mandayam V. Parthasarathy; Richard D. Vierstra; Ray J. Wu (Planta, 2006)

Application of the Algebraic Difference Approach for Developing Self-Referencing Specific Gravity and Biomass Equations - Lewis Jordan; Ray Souter; Bernard Parresol; Richard F. Daniels (Forest Science, 2006)
Biomass estimation is critical for looking at ecosystem processes and as a measure of stand yield. The density-integral approach allows for coincident estimation of stem profile and biomass. The algebraic difference approach (ADA) permits the derivation of dynamic or nonstatic functions. In this study we applied the ADA to develop a self-referencing specific gravity function and biomass function as part of a density-integral system composed of taper, volume, specific gravity, and biomass functions. This was compared to base systems of similar equations that did not have the self-referencing parameter specifications. Systems of equations were fit using nonlinear, seemingly unrelated regressions with nonlinear cross-equation constraints to account for contemporaneous correlations in the data. Results suggest that correct volume determination is more critical than specific gravity for accurate biomass estimates. The goodness-of-fit statistics clearly show that the self-referencing system provided a better fit than the base system.

Parsimonious and Completely Compatible Taper, Total, and Merchantable Volume Models - Lewis Jordan; Kenneth Berenhaut; Ray Souter; Richard F. Daniels (Forest Science, 2005)
A parsimonious and compatible system of taper, total, and merchantable volume equations sharing a common vector of three parameter estimates was derived from Clark and Saucier's (1990) volume ratio model. Clark and Saucier's model expresses volume inside bark as a function of outside bark diameter and is itself not compatible with the derived taper equation. To ensure compatibility, models were fit to express volume outside bark as functions of diameter outside bark. By constraining the limits of integration of the taper function to go from the tip to groundline diameter, a completely compatible system of taper, total, and merchantable volume equations were developed. Systems of equations were fit using nonlinear seemingly unrelated regressions with nonlinear cross-equation constraints to account for contemporaneous correlations in the data. The system fit was found to account for at least 96% of the variation in diameter outside bark, total, and merchantable outside bark volume. FOR. SCI. 51(6):578–584.

A Brief Overview of Tides in the Indonesian Seas - Richard Ray; Gary Egbert; Svetlana Erofeeva (Oceanography, 2005)

The development of volcanic hosted massive sulfide and barite–gold orebodies on Wetar Island, Indonesia - Philip M. Scotney; Stephen Roberts; Richard J. Herrington; Adrian J. Boyce; Ray Burgess (Mineralium Deposita, 2005)

Comments on the paper ?Spatial and temporal variability in excessive soil phosphorus levels in Eastern North Carolina? by Cahoon and Ensign - David H. Hardy; Richard C. Reich; M. Ray Tucker (Nutrient Cycling in Agroecosystems, 2005)

Comments on the paper ?Spatial and temporal variability in excessive soil phosphorus levels in eastern North Carolina? by Cahoon and Ensign - David H. Hardy; Richard C. Reich; M. Ray Tucker (Nutrient Cycling in Agroecosystems, 2004)

Growth, physiology, and chemistry of mycorrhizal and nonmycorrhizalTypha latifolia seedlings - Ryan M. Dunham; Andrew M. Ray; Richard S. Inouye (Wetlands, 2003)

Development of gypsy moth larvae feeding on red maple saplings at elevated CO 2 and temperature - Ray S. Williams; David E. Lincoln; Richard J. Norby (Oecologia, 2003)

Multiple conserved 5′ elements are required for high-level pollen expression of the Arabidopsis reproductive actin ACT1 - Angela Vitale; Ray J. Wu; Zaiquan Cheng; Richard B. Meagher (Plant Molecular Biology, 2003)

Developmental toxicity of pyrethroids - Bala Muhammad; Richard Verschoyle; David Ray (Archives of Toxicology, 2003)

Avenues for increasing salt tolerance of crops, and the role of physiologically based selection traits - Rana Munns; Shazia Husain; Anna Rita Rivelli; Richard A. James; A.G. Condon; Megan P. Lindsay; Evans S. Lagudah; Daniel P. Schachtman; Ray A. Hare (Plant and Soil, 2002)

Integrated Two-Dimensional Modeling of Fluid Flow and Compaction in a Sedimentary Basin - Zhangxin Chen; Richard E. Ewing; Hao Lu; Stephen L. Lyons; Serguei Maliassov; Michael B. Ray; Tong Sun (Computational Geosciences, 2002)

Tracing the Sources of Exported Nitrate in the Turkey Lakes Watershed Using 15 N/ 14 N and 18 O/ 16 O isotopic ratios - John Spoelstra; Sherry L. Schiff; Richard J. Elgood; Ray G. Semkin; Dean S. Jeffries (Ecosystems, 2001)

Inactivation of macaque lateral intraparietal area delays initiation of the second saccade predominantly from contralesional eye positions in a double-saccade task - Chiang-Shan Ray Li; Richard A. Andersen (Experimental Brain Research, 2001)

Effects of elevated CO 2 and temperature‐grown red and sugar maple on gypsy moth performance - Ray S. Williams; Richard J. Norby; David E. Lincoln (Global Change Biology, 2000)
Summary Few studies have investigated how tree species grown under elevated CO 2 and elevated temperature alter the performance of leaf‐feeding insects. The indirect effects of an elevated CO 2 concentration and temperature on leaf phytochemistry, along with potential direct effects on insect growth and consumption, may independently or interactively affect insects. To investigate this, we bagged larvae of the gypsy moth on leaves of red and sugar maple growing in open‐top chambers in four CO 2 /temperature treatment combinations: (i) ambient temperature, ambient CO 2 ; (ii) ambient temperature, elevated CO 2 (+ 300 μL L −1 CO 2 ); (iii) elevated temperature (+ 3.5°C), ambient CO 2 ; and (iv) elevated temperature, elevated CO 2 . For both tree species, leaves grown at elevated CO 2 concentration were significantly reduced in leaf nitrogen concentration and increased in C: N ratio, while neither temperature nor its interaction with CO 2 concentration had any effect. Depending on the tree species, leaf water content declined (red maple) and carbon‐based phenolics increased (sugar maple) on plants grown in an enriched CO 2 atmosphere. The only observed effect of elevated temperature on leaf phytochemistry was a reduction in leaf water content of sugar maple leaves. Gypsy moth larval responses were dependent on tree species. Larvae feeding on elevated CO 2 ‐grown red maple leaves had reduced growth, while temperature had no effect on the growth or consumption of larvae. No significant effects of either temperature or CO 2 concentration were observed for larvae feeding on sugar maple leaves. Our data demonstrate strong effects of CO 2 enrichment on leaf phytochemical constituents important to folivorous insects, while an elevated temperature largely has little effect. We conclude that alterations in leaf chemistry due to an elevated CO 2 atmosphere are more important in this plant–folivorous insect system than either the direct short‐term effects of temperature on insect performance or its indirect effects on leaf chemistry.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Leukemias and lymphomas: time trends in the UK, 1984–93 - Richard J.Q. McNally; Eve Roman; Ray A. Cartwright (Cancer Causes & Control, 1999)

Leaf age effects of elevated CO 2 ‐grown white oak leaves on spring‐feeding lepidopterans - RaY. S. Williams; David E. Lincoln; Richard J. Norby (Global Change Biology, 1998)
Folivorous insect responses to elevated CO 2 ‐grown tree species may be complicated by phytochemical changes as leaves age. For example, young expanding leaves in tree species may be less affected by enriched CO 2 ‐alterations in leaf phytochemistry than older mature leaves due to shorter exposure times to elevated CO 2 atmospheres. This, in turn, could result in different effects on early vs. late instar larvae of herbivorous insects. To address this, seedlings of white oak ( Quercus alba L.), grown in open‐top chambers under ambient and elevated CO 2 , were fed to two important early spring feeding herbivores; gypsy moth ( Lymantria dispar L.), and forest tent caterpillar ( Malacosoma disstria Hübner). Young, expanding leaves were presented to early instar larvae, and older fully expanded or mature leaves to late instar larvae. Young leaves had significantly lower leaf nitrogen content and significantly higher total nonstructural carbohydrate:nitrogen ratio as plant CO 2 concentration rose, while nonstructural carbohydrates and total carbon‐based phenolics were unaffected by plant CO 2 treatment. These phytochemical changes contributed to a significant reduction in the growth rate of early instar gypsy moth larvae, while growth rates of forest tent caterpillar were unaffected. The differences in insect responses were attributed to an increase in the nitrogen utilization efficiency (NUE) of early instar forest tent caterpillar larvae feeding on elevated CO 2 ‐grown leaves, while early instar gypsy moth larval NUE remained unchanged among the treatments. Later instar larvae of both insect species experienced larger reductions in foliage quality on elevated CO 2 ‐grown leaves than earlier instars, as the carbohydrate:nitrogen ratio of leaves substantially increased. Despite this, neither insect species exhibited changes in growth or consumption rates between CO 2 treatments in the later instar. An increase in NUE was apparently responsible for offsetting reduced foliar nitrogen for the late instar larvae of both species.

Relationships of chestnut species and New Zealand chestnut selections using morpho-nut characters - Nnadozie C. Oraguzie; David L. McNeil; David J. Klinac; Ray D. Knowles; J. Richard Sedcole (Euphytica, 1998)

The role of biomineralization in microbiologically influenced corrosion - Brenda Little; Patricia Wagner; Kevin Hart; Richard Ray; Dennis Lavoie; Kenneth Nealson; Carmen Aguilar (Biodegradation, 1998)

Effects of elevated CO 2 ‐grown loblolly pine needles on the growth, consumption, development, and pupal weight of red‐headed pine sawfly larvae reared within open‐topped chambers - RAY WILLIAMS; DAVID LINCOLN; RICHARD THOMAS (Global Change Biology, 1997)
Seedlings of loblolly pine, Pinus taeda , were grown in open‐topped chambers under four levels of CO 2 : two ambient and two elevated. Larvae of the red‐headed pine sawfly, Neodiprion lecontei , were reared from early instar to pupation, primarily on branches within chambers. Larval growth and mortality were assessed and leaf phytochemistry samples of immature and mature leaves collected weekly. Mature leaves grown under elevated CO 2 had significant reductions in leaf nitrogen and increases in non‐structural carbohydrate contents, resulting in foliage being a poorer food source for larvae, i.e. higher carbohydrate:nitrogen ratio. Nutritional constituents of immature needles were unaffected by seedling CO 2 treatment. Volatile mono‐ and sesquiterpenes were unrelated to plant CO 2 treatments for either leaf age class. Larval consumption of immature needles significantly increased on seedlings grown under CO 2 enrichment, while mature needle consumption was not different between the treatments. The average weight gain per larva significantly declined in late instar larvae consuming elevated CO 2 ‐grown needles. In spite of this reduced growth, neither the days to pupation nor pupal weights were different among the CO 2 treatments. This study suggests that enriched CO 2 ‐induced alterations in pine needle phytochemistry can affect red‐headed pine sawfly performance. However, compensatory measures by larvae, such as choosing to consume more nutritious immature needles, apparently helps offset enriched CO 2 ‐induced reductions in the leaf quality of mature needles.

The relationship between ecology and the incidence of cooperative breeding in Australian birds - Hugh A. Ford; Harry Bell; Ray Nias; Richard Noske (Behavioral Ecology and Sociobiology, 1988)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)